Strategi Pengembangan Kualitas Jasa Transportasi Terhadap Keputusan Pelanggan Studi Kasus pada PT. Eka Sari Lorena Transport - Mubarak, Mumuh Mulyana; Marpaung, Bintang Sahala (Jurnal Ilmiah Kesatuan (JIK), 2010)
Competition in the business world, especially transportation are increasingly stringent, so that any business carried on by a company There are many challenges and obstacles. To overcome this, companies can establish a good business strategy and perfect in practice. One of the main objectives of the company in the marketing concept is to provide satisfaction for each of its customers so the company can maintain the viability of their business and continue to grow in the long run. The main purpose of this study was to determine how much influence Quality of Service Against Decision customers. Variables used in this study is the independent variable is the quality of transport services consisting of being, reliability, responsibility, assurance, empathy. While the dependent variable is the Customer Decision. The results showed that the influence of the quality of transport services is influencing the decisions of customers. While the results of an analysis of how the influence, the quality of transport services is known that the correlation coefficient of 0.695. This shows a strong relationship between quality of service to the customers decision. Direction of a positive relationship (no negative sign in the figure 0.695) showed better quality of services created, the higher the customers decision to use the services PT.Eka Sari Lorena Transport. Vice versa, the worse the quality of services, then the lower the customers decision to use the services of PT. Eka Sari Lorena Transport significant level of correlation one side of the juice output (measured by probability) produce numbers 0,000. Therefore probabilatas above 0.05 then the correlation between the quality of customer service and significant decisions. Influence the quality of service to the customers decision for R = 0.695 means very influential. While the percentage of influence between the quality of transport services and the customers decision was seen from the R square = 0.483 or 48.3%. That means the customers decision affected the quality of transport services by 48.3%. And the remaining 43.8% are influenced by other factors. The regression equation to test the effect of x on y is as follows:, the constant of 11.114 states that if there is no quality of service the customers decision of 15.114. Regression coefficient of 1.991 states that any additional increase / decrease by 1 unit then the quality of services will result in an increase / decrease in the dependent variable (Y) of 1.991 with a constant of 15.114.